PENGARUH PERKEMBANGAN SEKTOR PARIWISATA, IPM, TENAGA KERJA SEKTOR PERTANIAN TERHADAP PDRB SEKTOR PERTANIAN KOTA BATU TAHUN 2003-2020 - Zulfikar Muhamad Hanif; Fadil, Faishal (Journal of Development Economic and Social Studies, 2023)
Batu City is a city that has fertile soil and is suitable for planting various kinds of plants and is suitable for the development of the agricultural sector. Batu City's agricultural sector plays an important role in absorbing labor, forming the GRDP of Batu City and supporting the development of other sectors. However, in recent years the growth of the Batu City agricultural sector has continued to slow down and the contribution of the Batu City agricultural sector to GRDP has continued to decline. On the other hand, the Tourism Sector is currently a sector that is growing rapidly in Batu City where the number of tourists and hotel buildings continues to increase from year to year. In addition, the Human Development Index (IPM) in Batu City also continues to increase and is in the good category. This study aims to determine how the influence of the number of tourists, the average length of stay at the hotel, the occupancy rate of hotel rooms, the human development index and the number of agricultural sector workers on the GRDP of the agricultural sector in Batu City. The results of the study found that the number of tourists had a positive and significant effect on the GRDP of the agricultural sector of Batu City, while the average length of stay at the hotel, the occupancy rate of hotel rooms, the human development index, and the number of workers in the agricultural sector has no significant effect on GRDP in Batu City.